Habitat ecology thinking in architecture - Heuvel, Dirk van den 1968-; Martens, Janno; Muñoz Sastre, Maria Teresa (nai010 publishers, 2020)
Today, under the pressure of climate change and ecological catastrophe, environmentalism has become a key driver to rethink the architectural discipline. The publication 'Habitat: Ecology Thinking in Architecture' aims to highlight some of the historical sources of ecological approaches that are currently reshaping the architectural field. The book will point out the paradigmatic shift in thinking about the built environment as something inherently contextual and relational. By demonstrating the continuities, disruptions and transformations at stake, the book will deepen the ongoing conversations, while suggesting directions for future research.00Based on selections from the archival resources of the national collection of Het Nieuwe Instituut in Rotterdam, and with additional materials from international archives, the book presents a lavish documentation of design proposals and research projects that map key positions since the 1950s, when the idea of ?habitat? was first investigated to reconceptualize architecture and its larger purpose, especially in the circles of the CIAM and Team 10
Seite 25 mit einem montierten Blatt (in Leporello-Faltung)
Enthält Index
Keywords: Team 10; International Congress for Modern Architecture; Geschichte 1950-2020; Umweltschutz; Städtebau; Ökologie; Architektur